6th International Symposium on Molecular Allergology (ISMA). Issue 2 (October 2016) - Hilger, Christiane; Swiontek, Kyra; Fischer, Jörg; Hentges, François; Lehners, Christiane; Morisset, Martine; Eberlein, Bernadette; Biedermann, Tilo; Ollert, Markus; Wildner, Sabrina; Stemeseder, Teresa; Freier, Regina; et al.
Table of contents ORAL ABSTRACTS Symposium 1: Biochemistry, structure and environment of the allergen: what makes a protein an allergen? O1 Two cell-membrane peptidases carrying galactose-alpha-1, 3-galactose are implicated in delayed anaphylactic reactions upon pork kidney ingestion in patients with IgE-antibodies to alpha-Gal Christiane Hilger, Kyra Swiontek, Jörg Fischer, François Hentges, Christiane Lehners, Martine Morisset, Bernadette Eberlein, Tilo Biedermann, Markus Ollert O2 Structure solution of Pla l 1 suggests similar folding of Ole e 1-like family members but distinct immunological properties Sabrina Wildner, Teresa Stemeseder, Regina Freier, Peter Briza, Roland Lang, Eva Batanero, Mayte Villalba, Jonas Lidholm, Thomas Hawranek, Fatima Ferreira, Hans Brandstetter, Gabriele Gadermaier Symposium 2: New allergen molecules in the spotlight O3 Identification of the cysteine protease Amb a 11 as a novel major allergen from short ragweed (Ambrosia artemisiifolia ) Philippe Moingeon, Rachel Groeme, Julien Bouley, Véronique Bordas, Maxime Le Mignon, Laetitia Bussières, Aurélie Lautrette, Laurent Mascarell, Vincent Lombardi, Véronique Baron-Bodo, Henri Chabre, Thierry Batard, Emmanuel Nony O4 Production and characterization of polybia paulista recombinant antigen 5: a valuable diagnostic tool Karine Marafigo De Amicis, Alexandra Sayuri Watanabe, Daniele Danella Figo, José Roberto Aparecido Dos Santos-Pinto, Mario Sergio Palma, Fabio Fernandes Morato Castro, Jorge Kalil, Therese Wohlschlager, Peter Briza, Sabrina Wildner, Fatima Ferreira-Briza, Gabriele Gadermaier, Keity Souza Santos Symposium 3: Progress in molecular and cellular diagnosis O5 Basophil activation test with recombinant Pru p 3; identifying genuine peach allergic patients Margaretha Faber, Athina Van Gasse, Vito Sabato, Margo M. Hagendorens, Chris H. Bridts, Luc S. De Clerck, Araceli Diaz Perales, Didier Ebo O6 Nanofluidic technology enables rapid, near-patient quantification of allergen-specific IgE Petra Zavadakova, Aurélie Buchwalder, Fabien Rebeaud, Iwan Märki Symposium 4: Relevance of molecular diagnostics for intervention and treatment O7 Longitudinal analysis of Bet v 1-specific epitope repertoires during birch pollen immunotherapy Barbara Gepp, Nina Lengger, Christian Möbs, Wolfgang Pfützner, Christian Radauer, Barbara Bohle O8 A natural CCD-free tool: is polistes sp. venom suitable for polybia paulista diagnosis and therapy? Karine Marafigo De Amicis, Alexandra Sayuri Watanabe, Clovis Eduardo Galvao, Daniele Danella Figo, Jose Roberto Aparecido Santos-Pinto, Mario Sergio Palma, Fabio Fernandes Morato Castro, Jorge Kalil, Fatima Ferreira, Gabriele Gadermaier, Keity Souza Santos Symposium 5: The advent of molecular allergology in epidemiology O9 Peanut oleosins: from identification to diagnostic testing Christian Schwager, Skadi Kull, Frauke Schocker, Jochen Behrends, Wolf-Meinhard Becker, Uta Jappe O10 Endotypes of oral allergy syndrome in childhood: a molecular diagnostic approach Carla Mastrorilli, Salvatore Tripodi, Carlo Caffarelli, Riccardo Asero, Arianna Dondi, Giampaolo Ricci, Carlotta Povesi Dascola, Elisabetta Calamelli, Andrea Di Rienzo Businco, Annamaria Bianchi, Tullio Frediani, Carmen Verga, Iride Dello Iacono, Diego Peroni, Giuseppe Pingitore, Roberto Bernardini, Paolo Maria Matricardi Symposium 6: Molecular AIT: which approaches will make it to market? O11 Mbc4: an innovative molecule to tackle birch pollen and concomitant food allergies Heidi Hofer, Claudia Asam, Michael Hauser, Peter Briza, Martin Himly, Christof Ebner, Fatima Ferreira O12 Challenges and solutions associated with the production of recombinant Bet v 1 allergen as a therapeutic protein Emmanuel Nony, Maxime Le Mignon, Pierrick Lemoine, Karine Jain, Kathy Abiteboul, Monica Arvidsson, Sabina Rak, Philippe Moingeon Clinical Cases: Breakthroughs and headaches from CRD: interactive session CC1 Anaphylaxis caused by lipid transfer proteins: a complex clinical pattern syndrome Inês Mota, Filipe Benito Garcia, Angela Gaspar, Cristina Arêde, Susana Piedade, Graça Sampaio, Graça Pires, Luís Miguel Borrego, Cristina Santa-Marta, Mário Morais-Almeida CC2 IgE sensitization profile in a patient with asteraceae pollen-exotic fruits association Florin-Dan Popescu, Mariana Vieru, Florin-Adrian Secureanu CC3 Food-dependent: exercise induced anaphylaxis. Which component to blame? Rosa Anita Rodrigues Fernandes, Isabel Carrapatoso, Raquel Gomes, Celso Pereira, Ana Todo-Bom CC4 Anaphylaxis to intravenous iron preparations in a patient that tolerates oral administration María Cecilia Martín Fernández De Basoa, Javier Barrios Regio, Juan De Castro Cordova, Antón Fernández Ferreiro CC5 IgE sensitization pattern in an adult patient with oral allergy syndrome to peanuts and pollinosis from southern Romania Florin-Dan Popescu, Mariana Vieru, Florin-Adrian Secureanu CC6 Evidence of specific IgE to plant-derived cross-reactive carbohydrate determinant in a patient with delayed anaphylaxis to red meat Mariana Vieru, Florin-Dan Popescu, Florin-Adrian Secureanu POSTER PRESENTATIONS Poster Session 1: Molecular allergology and epidemiology P1 Atopic children produce stronger and more frequent IgG responses than non-atopic children: longitudinal data from the German MAS birth cohort Olympia Tsilochristou, Serena Perna, Alina Schwarz, Alexander Rohrbach, Antonio Cappella, Laura Hatzler, Carl-Peter Bauer, Ute Hoffmann, Johannes Forster, Fred Zepp, Antje Schuster, Raffael D'amelio, Ulrich Wahn, Thomas Keil, Susanne Lau, Paolo Maria Matricardi P2 The IgG sensitization profiles against 112 allergenic components support the absence of a protective role of IgG in allergic individuals, outside of the context of SIT Pol André Apoil, Claire Mailhol, Anne Broué-Chabbert, Agnès Juchet, Alain Didier, Elodie Carrer, Thomas Lanot, Antoine Blancher P3 The immune response against the timothy grass pollen allergen Phl p 5 in non-allergic humans Almedina Kurtaj, Christoph Hillebrand, Gerda Fichtinger, Martin Danzer, Christian Gabriel, Theresa Thalhamer, Sandra Scheiblhofer, Josef Thalhamer, Richard Weiss P4 Analyzing the cross-reactivity profile of the major ragweed allergen Amb a 1 Martin Wolf, Michael Hauser, Ulrike Pichler, Teresa Twaroch, Gabriele Gadermaier, Christof Ebner, Hidenori Yokoi, Toshiro Takai, Alain Didierlaurent, Adriano Mari, Peter Briza, Heidrun Behrendt, Angela Neubauer, Frank Stolz, Fátima Ferreira, Michael Wallner P5 LTP (Pru p 3) sensitisation in skin prick test: which means in clinical practice? Sara Carvalho, Tatiana Lourenço, Joana Cosme, Fátima Cabral Duarte, Amélia Spínola Santos, Ana Célia Costa, Manuel Pereira Barbosa P6 IgE profiles, allergen exposure and lifestyle of 501 Austrian pupils: investigation of influences on the development of allergic sensitizations Teresa Stemeseder, Eva Klinglmayr, Bettina Schweidler, Lisa Lueftenegger, Stephanie Moser, Patrick Doppler, Roland Lang, Martin Himly, Gertie J. Oostingh, Arne Bathke, Joerg Zumbach, Thomas Hawranek, Gabriele Gadermaier P7 Molecular profiles of sensitization to perennial inhalant allergens in a middle European region Petr Panzner, Martina Vachova, Tomas Vlas, Marek Maly P8 Evolution of the IgE response to house dust mite allergen molecules in childhood Daniela Posa, Serena Perna, Stephanie Hofmaier, Laura Hatzler, Alexander Rohrbach, Carl-Peter Bauer, Ute Hoffmann, Johannes Forster, Fred Zepp, Antje Schuster, Philippe Stock, Ulrich Wahn, Linus Grabenhenrich, Thomas Keil, Susanne Lau, Kuan-Wei Chen, Yvonne Resch, Susanne Vrtala, Rudolf Valenta, Paolo Maria Matricardi P9 Tropomyosin (Pen a1): to include or not to include in skin prick testing? Joana Cosme, Sara Carvalho, Tatiana Lourenço, Amélia Spínola Santos, Manuel Pereira Barbosa Immunoallergy Department - Hospital de Santa Maria – Centro Hospitalar Lisboa Norte, Lisbon, Portugal, Lisbon, Portugal; Immunoallergy Department - Hospital de Santa Maria – Centro Hospitalar Lisboa Norte, Lisbon, Portugal; Faculdade de Medicina de Lisboa, Lisbon, Portugal P10 Component-resolved IgE profiles in Georgian patients Tamar Abramidze, Nino Lomidze, Maia Gotua P11 Cross reactivity between food and pollen allergens in Lithuania according to spIgE evaluation Austeja Dapkeviciute, Ruta Einikyte, Jolita Norkuniene, Laima Skrickiene, Asta Miskiniene, Violeta Kvedariene P12 Distribution of inhalant allergy in the population of Lithuania Ruta Einikyte, Austeja Dapkeviciute, Jolita Norkuniene, Laima Skrickiene, Asta Miskiniene, Violeta Kvedariene Poster Session 2: Allergen molecules: identification, characterization, structure and function P13 Interference of antigen 5-based cross-reactivity in the diagnosis of hymenoptera venom allergy Maximilian Schiener, Bernadette Eberlein, Carmen Moreno-Aguilar, Gunilla Pietsch, Mareike Mc Intyre, Lea Schwarze, Dennis Rußkamp, Tilo Biedermann, Edzard Spillner, Ulf Darsow, Carsten Schmidt-Weber, Markus Ollert, Simon Blank P14 IgE cross-reactivity between European Hymenoptera and Asian hornet (Vespa velutina ) venom allergens Cyril Longé, Andrea Brazdova, Jean-Louis Brunet, Claire Schwartz, Bruno Girodet, François Lavaud, Joelle Birnbaum, Nhân Pham Thi, Magalie Duchateau, Julia Chamot-Rooke, Laurence Guilloux, Marie-Ange Selva, Rémy Couderc, Hélène Sénéchal, Jean-Pierre Sutra, Pascal Poncet P15 Carbohydrate composition of house dust mite extracts and major group 1 and group 2 allergens Steffen Augustin, Linda Pump, Martin Wald, Thomas Eichhorn, Frank Fischer, Christoph Willers P16 Specificity of monoclonal antibodies against cross-reactive carbohydrate determinants Michaela Miehe, Melanie Plum, Sara Wolf, Frederic Jabs, Tim Raiber, Frank Bantleon, Henning Seismann, Thilo Jakob, Edzard Spillner P17 Red meat allergic patients have a selective IgE response to the a-Gal glycan Danijela Apostolovic, Anh Thu Tran, Sara Sanchez-Vidaurre, Tanja Cirkovic Velickovic, Maria Starkhammar, Carl Hamsten, Marianne Van Hage P18 Specificity of non-specific lipid transfer proteins and influence of the ligands on their three-dimensional structure Pawel Dubiela, Piotr Humeniuk, Sabine Pfeifer, Merima Bublin, Tomasz Borowski, Karin Hoffmann-Sommergruber P19 Real-time PCR analysis of Pru av 1 and Pru av 3 allergens Martie C.M. Verschuren, Shanna Bastiaan-Net, Defien Depoortere, Kay Foetisch, Stephan Scheurer, Harry J Wichers, Theo Noij P20 Specificity of anti-Pru av 1 antibodies for the detection of Pru av 1 isoallergens Martie C.M. Verschuren, Shanna Bastiaan-Net, Nikki M.E. Van Uden, Karel Vandenberghe, Kay Foetisch, Stephan Scheurer, Harry J. Wichers H.J., Theo H.M. Noij P21 Enhancing recombinant production yield of Bet v 1 through codon usage harmonization Anargyros Roulias, Maria Alejandra Parigiani, Heidi Hofer, Claudia Asam, Christof Ebner, Fátima Ferreira P22 Structural and dynamic insights into the world of PR-10 allergens Linda Ahammer, Sarina Grutsch, Martin Tollinger Poster Session 3: Allergen molecules: identification, characterization, structure and function P23 Purification of polcalcin from different pollen allergenic sources by antibody-affinity chromatography Raquel Moya, Mª Angeles López-Matas, Raquel Reyes, Jerónimo Carnés P24 Variations of wheat allergens in cultivars measured through a targeted quantitative mass spectrometry approach Colette Larré, Hélène Rogniaux, Roberta Lupi, Sandra Denery-Papini P25 Art v 1, Amb a 4 and Par h 1 defensin-like proteins share similar structural features but distinct immunological and allergenic properties Isabel Maria Pablos, Stephanie Eichhorn, Yoan Machado, Peter Briza, Christof Ebner, Jung-Won Park, Alain Didierlaurent, Naveen Arora, Stefan Vieths, Gabriele Gadermaier, Fatima Ferreira P26 Homogeneity or diversity of IgE-binding proteins in wheat dependant exercise induced anaphylaxis? Sandra Denery-Papini, Charlene Tanaka, Florence Pineau, Roberta Lupi, Martine Drouet, Etienne Beaudouin, Martine Morisset, Susan Altenbach P27 Deciphering the role of disulfide bonds and of repetitive epitopes in immunoglobulin E binding to wheat gliadins Sandra Denery-Papini, Hamza Mameri, Chantal Brossard, Roberta Lupi, Florence Pineau, Jean Charles Gaudin, Denise Anne Moneret-Vautrin, Etienne Beaudouin, Evelyne Paty, Martine Drouet, Olivier Tranquet, Colette Larré P28 Assessment of the allergenicity of soluble fractions from bread and durum wheats genotypes Roberta Lupi, Stefania Masci, Olivier Tranquet, Denise-Anne Moneret-Vautrin, Sandra Denery-Papini, Colette Larré P29 Isolation and characterization of Ara h 12 and Ara h 13: defensins, a novel class of peanut allergens Skadi Kull, Arnd Petersen, Marisa Böttger, Sandra Rennert, Wolf-Meinhard Becker, Susanne Krause, Martin Ernst, Thomas Gutsmann, Johann Bauer, Buko Lindner, Uta Jappe P30 Allergenicity attributes of different peanut market types Stef Koppelman, Shyamali Jayasena, Dion Luykx, Erik Schepens, Danijela Apostolovic, Govardus De Jong, Tom Isleib, Julie Nordlee, Joe Baumert, Steve Taylor, Soheila Maleki P31 The impact of peanut lipids on Ara h 1-induced immune responses in monocytes-derived dendritic cells Chiara Palladino, Barbara Gepp, Sofía Sirvent, Alba Angelina, Merima Bublin, Christian Radauer, Nina Lengger, Thomas Eiwegger, Oscar Palomares, Heimo Breiteneder P32 Compared allergenicity of native and thermally aggregated ovalbumin as large agglomerated particles Mathilde Claude, Roberta Lupi, Grégory Bouchaud, Marie Bodinier, Chantal Brossard, Sandra Denery-Papini P33 Simulation of the gastrointestinal digestion of the hazelnut allergens Cor a 9 and Cor a 11 by an in-vitro model and characterisation of peptidic products including epitopes by HPLC-MS/MS Robin Korte, Julia Bräcker, Jens Brockmeyer P34 Analysis of distribution of rice allergens in brown rice grain and allergenicity of the products containing rice bran Rie Satoh, Reiko Teshima Poster Session 4: Molecular approaches in AIT P35 Production of a recombinant hypoallergenic variant of the major peanut allergen Ara h 2 for allergen-specific immunotherapy Angelika Tscheppe, Dieter Palmberger, Merima Bublin, Christian Radauer, Chiara Palladino, Barbara Gepp, Nina Lengger, Reingard Grabherr, Heimo Breiteneder P36 Mutagenesis of amino acids critical for calcium-binding leads to the generation of a hypoallergenic Phl p 7 variant Marianne Raith, Linda Sonnleitner, Doris Zach, Konrad Woroszylo, Margit Focke-Tejkl, Herbert Wank, Thorsten Graf, Annette Kuehn, Ines Swoboda P37 Are birch pollen allergen immunotherapy induced blocking antibodies protective for cross-reactive allergens? Claudia Asam, Sara Huber, Heidi Hofer, Roland Lang, Thomas Hawranek, Fátima Ferreira, Michael Wallner P38 High success of 58 subcutaneous immunotherapy for pets allergy in a polyallergic cohort of patients: a component resolved individually adapted treatment (CRIAT) Fabienne Gay-Crosier P39 Neutrophils are potential antigen presenting cells in IgE- mediated allergy Dominika Polak, Birgit Nagl, Claudia Kitzmüller, Barbara Bohle P40 Characterization of allergen-specific CD8+ T cells in type I allergy Nazanin Samadi, Claudia Kitzmüller, Rene Geyeregger, Barbara Bohle, Beatrice Jahn-Schmid Poster Session 5: Molecular and cellular diagnostic tests P41 Nanofluidic-based biosensors allow quantification of total circulating IgE from a drop of blood in 5 minutes Aurélie Buchwalder, Ariel Gomez, Fabien Rebeaud, Iwan Märki P42 Allergen microarray for the analysis of serum IgE binding profile and allergenic activity Jaana Haka, Liisa Hattara, Marika Heikkinen, Merja H Niemi, Juha Rouvinen, Petri Saviranta, Pekka Mattila, Kristiina Takkinen, Marja-Leena Laukkanen P43 Generation of a well-characterized panel of periplaneta americana allergens for component resolved diagnosis Stephanie Eichhorn, Isabel Pablos, Bianca Kastner, Bettina Schweidler, Sabrina Wildner, Peter Briza, Jung-Won Park, Naveen Arora, Stefan Vieths, Gabriele Gadermaier, Fatima Ferreira P44 Improved diagnostic sensitivity of recombinant Api m 1 and Ves v 5 in diagnosis of Hymenoptera venom allergy Mira Silar, Julij Selb, Rok Kogovsek, Mitja Kosnik, Peter Korosec P45 Added value of biomarkers of primary sensitization and cross-reactivity in patients with hymenoptera venom allergy Leticia Pestana, Alcinda Campos Melo, Ana Mendes, Maria Elisa Pedro, Manuel Pereira Barbosa, Maria Conceição Pereira Santos P46 Cosensitization to Alt a 1 and Act d 2: more than a fortuitous association? Françoise Bienvenu, Claire Goursaud, Lorna Garnier, Sandrine Jacquenet, Michaël Degaud, Sébastien Viel, Annick Barre, Pierre Rougé, Jacques Bienvenu, Joana Vitte P47 Molecular diagnosis for peanut allergy: ALFA method performs as well as established methods for Ara h 1, Ara h 2, Ara h 6, Ara h 9 and CCD Amel Bensalah, Isabelle Cleach, Laurent Mousseau, Chantal Agabriel, Valérie Liabeuf, Joëlle Birnbaum, Jean-Louis Mège, Joana Vitte P48 Evaluation of a food challenge service in relation to specific IgE to molecular components in children with suspected peanut allergy James Gardner, Minal Gandhi, Harsha Kariyawasam, Giuseppina Rotiroti P49 Component resolved diagnosis in cereal allergy Isabel Carrapatoso, Celso Pereira, Frederico Regateiro, Emília Faria, Ana Todo-Bom Poster Session 6: Molecular diagnosis in prevention and therapy P50 Pretreatment molecular sensitizations determine the sIgG4 induction during the updosing of SCIT and may be useful to identify clinically relevant additional sensitizations Johannes Martin Schmid, Ronald Dahl, Hans Juergen Hoffmann P51 Usefulness of recombinant latex allergens in immunotherapy's decision and follow-up Inês Mota, Filipe Benito Garcia, Angela Gaspar, Mário Morais-Almeida P52 Omega-5-gliadin in the diagnosis of wheat-dependent anaphylaxis induced by ibuprofen but not by exercise Joana Cosme, Letícia Pestana, Amélia Spínola Santos, Manuel Pereira Barbosa P53 Food dependent exercise-induced anaphylaxis: a component-resolved and in vitro depletion approach to access IgE cross-reactivity Diana Silva, Teresa Vieira, Ana Maria Pereira, André Moreira, Luís Delgado P54 Olive pollen allergens: what are we missing? Sara Prates, Cátia Alves, Elena Finelli, Paula Leiria Pinto P55 Purified Alt a 1 extract inAlternaria alternata allergy diagnosis Bárbara Kong Cardoso, Cíntia Cruz, Filipa Semedo, Elza Tomaz, Filipe Inácio P56 Use of specific IgE Bos d8 (casein) to aid early introduction of dietary baked milk in children with cows' milk allergy James Gardner, Santanu Maity, Giuseppina Rotiroti, Minal Gandhi P57 Molecular characterisation and immunoreactivity of a peanut ingredient for use in oral food challenges Ivona Baricevic-Jones, Justin T. Marsh, Phil E. Johnson, Anuradha Balasundaram, Anya-May Hope, Aafke Taekema, Angela Simpson, Aida Semic-Jusufagic, E.N. Clare Mills P58 Specific IgE to recombinant allergens of hazelnut and oral food challenge in children Gourdon Dubois Nelly, Sellam Laetitia, Pereira Bruno, Michaud Elodie, Messaoudi Khaled, Evrard Bertrand, Fauquert Jean-Luc Poster session 7/8: miscellaneous P59 What defines a protein as an allergen? A discussion of sources and sufficiency Richard E. Goodman P60 Cat allergy: relationship between clinical and molecular diagnostic María Cecilia Martín Fernández De Basoa, Antón Fernández Ferreiro, Elena Rodríguez Plata P61 Anaphylaxis to rabbit: the cat came in last Luis Amaral, Borja Bartolomé, Alice Coimbra, Jose L Placido P62 Dog allergy: relationship between clinical and molecular diagnostic María Cecilia Martín Fernández De Basoa, Antón Fernández Ferreiro, Elena Rodríguez Plata P63 Correlation of serum timothy grass-pollen specific IgE levels determined by two immunoblot test systems Mariana Vieru, Florin-Dan Popescu, Florin-Adrian Secureanu, Carmen Saviana Ganea P64 Development of oral food challenge formulations for diagnosis of fish allergy using powdered fish ingredients Carol Ann Costello, Ivona Baricevic-Jones, Martin Sorensen, Clare Mills, Adrian Rogers, Aage Otherhals P65 Fish and peanut allergens interact with plasma membranes of intestinal and bronchial epithelial cells and induce differential gene expression of cytokines and chemokines Tanja Kalic, Isabella Ellinger, Chiara Palladino, Barbara Gepp, Eva Waltl, Verena Niederberger-Leppin, Heimo Breiteneder P66 Interleukin 4 affects fat tissue metabolism and expression of pro-inflammatory factors in isolated rat adipocytes Dawid Szczepankiewicz, Ewa Pruszynska-Oszmalek, Marek Skrzypski, Krzysztof W. Nowak, Aleksandra Szczepankiewicz P67 Ozone induced airway hyperreactivity in PD-L2−/− mice model Gwang-Cheon Jang P68 Thymic stromal lymphopoietin (TSLP) and its receptor as targets for the development of anti-inflammatory inhibitory agents Iva Markovic, Andreas Borowski, Tina Vetter, Andreas Wohlmann, Michael Kuepper, Karlheinz Friedrich P69 The mononuclear phagocyte system in experimentally-induced allergic rhinitis Ibon Eguiluz Gracia, Anthony Bosco, Ralph Dollner, Guro Reinholt Melum, Anya C Jones, Maria Lexberg, Patrick G Holt, Espen Sønderaal Bækkevold, Frode Lars Jahnsen P70 Expression of histamine metabolizing enzymes is increased in allergic children Aleksandra Szczepankiewicz, Paulina Sobkowiak, Marta Rachel, Beata Narozna, Dorota Jenerowicz, Witold Swiatowy, Anna Breborowicz P71 Modifying the glycosylation of human IgE towards oligomannosidic structures does not affect its biological activity Melanie Plum, Sara Wolf, Frank Bantleon, Henning Seismann, Frederic Jabs, Michaela Miehe, Thilo Jakob, Edzard Spillner P72 Flying Labs: an educational initiative to transfer allergy research into high-school settings Michael Wallner, Heidi Hofer, Fatima Ferreira, Reinhard Nestelbacher P73 Clinical significance of antihistamines and Kujin, an anti-allergic Kampo medicine Hiroyuki Fukui